The Impact of Organizational Development Initiatives on Business Performance - Hasyim, Hasyim; Bakri, Muhammad (Paradoks : Jurnal Ilmu Ekonomi, 2023)
This study investigates the impact of Organizational Development (OD) initiatives on business performance, addressing gaps in understanding how OD affects various performance dimensions in the short and long term. A qualitative approach through a comprehensive literature review was employed, utilizing thematic analysis and narrative synthesis to explore the effectiveness of OD initiatives such as training, leadership development, and change management across different organizational contexts. The analysis reveals that OD initiatives significantly enhance employee engagement, productivity, and morale in the short term, while contributing to financial performance, market positioning, and organizational resilience in the long term. Key factors influencing the success of these initiatives include organizational culture, industry dynamics, and organizational size. This study provides actionable insights for practitioners to design effective OD strategies and underscores the importance of aligning these initiatives with organizational goals and contextual factors to achieve sustainable growth and competitive advantage.